We Can Do Better: Building Competencies until Graduation - Payan-Carreira, Rita (2019)
Today’s global economy requests from graduates that they have the competencies at day-1 suiting the workplace, including critical thinking,adaptability, autonomy, teamwork and communication. These competencies go beyond the cognitive achievements or the content knowledge that are often identify as major outcomes in multiple tertiary education providers worldwide. According to published surveys, the hardest positions to fill still require from graduates a combination of technical and transferable soft skills, suggesting that in most cases Higher Education Institutions (HEI) still have difficulties in reaching such a prime goal. It is often claimed that a skills’ gap exists between the expectations of employers and HEI regarding the competencies that should be mastered by graduates at the entrance in the labor market. However, even if this opinion is not consensual, and in an attempt to bridge this gap, several initiatives and recommendations have emerged in different countries through the implementation of educational policies and frameworks. In Europe, this has led to the adoption of the philosophy endorsed in the Bologna reform and the Miller pyramid framework for assessment. This skills’ gap is evolutive and may present different forms amongst countries or professions. Results from an Erasmus+ project (CRITHINKEDU - Critical Thinking Across the European Higher Education Curricula) have shown that those skills may vary between professional fields, particularly on how they are understood and applied (Dominguez 2018). Moreover, the increased complexity of the professional reality and the tremendous pace at which technology evolves, hinder the efforts taken by the higher education institutions and delay the implementation of adaptative strategies that will foster a constant fitting of the undergraduates to the workplace requirements. The needed adaptation of the HEI is crucial to ensure that their graduates succeed in the current highly competitive professional market. In this sense, and believing that we can do better to drive this change, the current chapter discusses some pathways available to HEI towards the assessment of needs and the improvement of course planning, curriculum design and student guidance systems. It will contribute to present/discuss pathways to reduce the existing gaps between day-1 graduates and labor market demands (degree-job match). The complex and multidimensional challenges need to be faced together by higher education and the labor market, as a shared responsibility in establishing educational goals, providing settings and discussing the assessment of outcomes. Such cooperation should also allow to preview for competency-shifts attending to the rapid technological changes, economic and cultural globalization.